2017
DOI: 10.21608/epx.2018.7011
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and its association with insomnia and clinical variables in type 2 diabetes

Abstract: Background: There is a significant increase in number of patients with type II diabetes, Quality of Life (QOL) has become a major concern. Insomnia associated with diabetes may also influence QOL in these patients. Aim: This cross sectional comparative study aims to assess QOL and its determinants inpatients with type 2 diabetes (T2DM). It also explored the prevalence and association of insomnia with QOL in T2DM patients. Materials and Methods:The sample size comprised of 50 patients with T2DM and equal number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Furthermore, in people with diabetes or hypertension, insomnia is associated with an increased mortality rate (OR 7.17 [95% CI 1.41, 36.62]) [ 12 ]. Finally, in addition to poorer health outcomes, and perhaps most important for patients, insomnia negatively affects QoL, affecting all domains of QoL questionnaires [ 13 , 14 ], compared with those with type 2 diabetes without insomnia.…”
Section: Prevalence and Health Outcomes Of Sleep Disorders In Type 2 Diabetesmentioning
confidence: 99%
“…Furthermore, in people with diabetes or hypertension, insomnia is associated with an increased mortality rate (OR 7.17 [95% CI 1.41, 36.62]) [ 12 ]. Finally, in addition to poorer health outcomes, and perhaps most important for patients, insomnia negatively affects QoL, affecting all domains of QoL questionnaires [ 13 , 14 ], compared with those with type 2 diabetes without insomnia.…”
Section: Prevalence and Health Outcomes Of Sleep Disorders In Type 2 Diabetesmentioning
confidence: 99%
“…Five case-control studies where diabetes respondents were compared with nondiabetes patients were identified,[ 26 35 36 37 38 ] whereas the remainder of studies were cross-sectional.…”
Section: R Esultsmentioning
confidence: 99%
“…Of the reviewed studies, only 14 reported gender and QoL. Poorer QoL in women than men were reported in nine studies on T2D[ 15 23 25 31 35 37 45 46 47 ] and in one study on T1D. [ 14 ] It is of interest that three studies had reported better QoL among female respondents with diabetes when compared to their male counterparts.…”
Section: R Esultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Insomnia has been shown to be associated with QOL in various populations such as cancer patients [21], patients with Type II diabetes [22]; and epilepsy [23].…”
Section: Qol Among Adolescents Living With Hivmentioning
confidence: 99%